Money capital & fluctuations / F.A. Hayek - Hayek, F. A.; Mccloughry, Roy (ed.) (London, 1984)
In 1931 Friedrich Hayek made his debut in England, giving four lectures at the London School of Economics which were to prove the fulcrum of his early work. Intensely analytical, the lectures caused a controversy in the economics profession and brought an explosion of interest in 'Austrian' economics. They were published in book form as Prices and Production, but since few English-speaking economists were familiar with Hayek's earlier writings, published in German, his contribution to the history of economic analysis in the 1930s has always been difficult to assess. These theories had, however, been developed in a series of studies during the preceding years. This collection of essays, brought together by Roy McCloughry and translated for the first time into English, gives a valuable opportunity to analyse the foundations of Hayek's extraordinary ability to make seminal contributions to several diverse areas - linking monetary and capital theory, the business cycle and the history of economic analysis - and to blend these into a cohesive whole.
Keywords: Money